FACTORS INFLUENCING DEVELOPMENT OF WOMEN ENTREPRENEURSHIP IN UNORGANIZED SECTOR IN MADURAI DISTRICT (International Journal of Psychosocial Rehabilitation, 2020)
With the development of micro, small, and medium enterprises, a huge number of women have entered into entrepreneurial activities and are experiencing significant success in recent times. Financial, market, moral, and social factors are factors influencing the development of women's entrepreneurship in the unorganized sector. Significant differences exist among factors influencing the development of women's entrepreneurship in the unorganized sector and their demographics. Market, financial, moral, and social factors have a significant and positive effect on the level of success of women entrepreneurs. Thus, banks and training institutes should give adequate loans to women entrepreneurs, and family, friends, and relatives must financially support women entrepreneurs. Women entrepreneurs should explore market opportunities and improve their accessibility to various markets. Women entrepreneurs must get marketing information from trade organizations and market reports, and they should utilize that information efficiently in order to improve the marketability of their products and services.